Measurement of Total Sugar Content of Residue from Bioenergy Pig Excreta in Marsh-Gas Sinks - Peng, G.; Davis, E.V.; Wang, L.X.; Zhang, C.W. (Asian Journal of Chemistry, 2013)
Marsh gas from pig excreta is considering as a new bioenergy. 30 marsh-gas sinks of pig excreta are used as samples in Nanhu area of Jiaxing in China. The material and the last residue are different between solution and insoluble substances. The study concerns to measure the total sugar content of residue from bioenergy pig excreta by 3,5-dinitrosalicylic acid. The main consequence shows that the residue contained sugar amount is 107.3 g/L. The method is helpful to improve the utilization efficiency of marsh-gas and extend a new way of circular economy and agricultural development.